Art education through movement: the corporal expression in physical education - Javier COTERÓN LÓPEZ; Galo SÁNCHEZ SÁNCHEZ (Ediciones Universidad de Salamanca, 2010)
Art Education in school provides values of creativity and aesthetic understanding to the training and development of the individual, linked intimately to the culture in which the educational act is framed. In this paper, we set out to extend the understanding of the artistic phenomenon through an approach to the movement education or physical education at school. In doing so, we will put forward the elements of the expressive dimension of movement and the contributions that Corporal Expression offers as a discipline with a strong relevance for the aesthetic and training experience of each student. This approach emphasizes the creative potential of motor activities and their value of implementation in the construction of collective scenic projects with expressive and communicative nature.